THE The Determinants of the Social Performance in the Microfinance Institutions (A case study of India and Pakistan) - Hassan, Wisal; Khan, Muhammad; zainullah (Journal of Business & Tourism, 2024)
There are two main goals of the microfinance institutions, the financial stability and the social performance. The welfare’s model of the microfinance institutions states that microfinance institute should increase the social performance by increasing the number of active borrowers as well as should increase the average loan per borrowers to the needy people of the society. There are numerous determinants that are related with the social performance. The study’s objective was to look at the aforementioned factors and how they affect social performance in Pakistan and India. The secondary sources for the data collection were used and the sources for the data collection were the annual reports of the microfinance institution. On the basis of Hausman test fixed effect model was suggested and according to the results age and firm size remain positive and significant with the social performance in both India and Pakistan. The credit remain negative but insignificant in India and Pakistan. It is the return on assets that has negative and significant relationship with the social performance in Pakistan which indicates that in Pakistan increase in the social performance will reduce the social performance but in the case of India it has no impact on the social performance. The research recommended that MFIs should increase the social performance in order to target more and more poor people in the country.